The Therapeutic Value of Recording in Music Therapy for Adult Clients in a Concurrent Disorders Inpatient Treatment Facility - Kirkland, Kevin; Nesbitt, Shannon (Voices: A World Forum for Music Therapy, 2019)
While recording has traditionally been viewed as a practical, adjunctive role of the music therapist, here the authors examine the skillful use of recording devices and software as fertile ground for the development of therapeutic programs with tangible benefits for adult clients in a concurrent disorders recovery setting. The integration and layering of musical composition with musical performance, digital technologies, and production, invite rich and engaging conversations about therapeutic goals, processes, and outcomes. Using methods of action research inquiry, the authors discuss how their interactions with clients through recording have yielded new insights into therapist roles and identities as well as expressions of music therapy. The case for therapy-oriented recording is outlined and a description of the authors’ research setting and data collection methods identified before a literature review on the use of recording in music therapy is provided. The authors then distinguish four types of therapeutic recording illustrated by case examples from work with clients. Their writing culminates with a discussion of challenges and benefits associated with therapeutic recording. The authors conclude that recording offers critical and rewarding yet often unrecognized opportunities for music therapists to be innovators in their field.